Barriers Towards Healthcare Access and Services among People with Disabilities: A Scoping Review of Qualitative Studies - Said, Abdul Hadi; Mohd, Farah Natashah; Baharom, Mohamad Zairi; Md Aris, Mohd Aznan; Mohamad Shahrin, Mohamad Afiq (IIUM Medical Journal Malaysia, 2024)
Healthcare access and services is one of the challenges faced by people with physical disability (PWPD). PWPD also has at risk of early death and preventable chronic illness. Lack of access to healthcare services includes delay or failure to receive needed care, lack of continuity of care and financial burden will result in deterioration of health, wellbeing and functional status. The aim of this paper was to review barriers towards healthcare access and services among PWPD based on the existing qualitative studies. We conducted a scoping review of relevant qualitative articles from PubMed, Scopus and ProQuest. The article search was based on the available keyword in the title with the publication restricted within 10 years (between 2012 to 2021). The search strategy was conducted using MeSH terms of ‘barriers, healthcare access, healthcare services and physical disability’. In this review, people with different kinds of physical disabilities were included. There were 2004 articles obtained from the initial search. 27 articles met the inclusion criteria for the final review. In each study, PWPD noted various barriers to access healthcare services. Findings from this review revealed five themes: personal; financial; attitudinal and communication; health system; structural and physical barriers. The findings showed that PWPD faces various barriers when accessing healthcare services. Addressing these barriers could help create a healthcare system that is inclusive and accessible for all.